Risk of Acute Asthma Attacks Associated With Nonsteroidal Anti-inflammatory Drugs: A Self-Controlled Case Series. (May 2017) - Takeuchi, Yoshinori; Ando, Takashi; Ishiguro, Chieko; Uyama, Yoshiaki
Background: Although asthma attacks are known adverse events associated with nonsteroidal anti-inflammatory drug (NSAID) use, few studies have quantified these risks. The objectives of this study were to utilize an epidemiological approach to quantitatively evaluate the risk of acute asthma attacks associated with NSAID prescription in Japan and to compare the risks among NSAIDs according to their cyclooxygenase (COX)–2 selectivity. Methods: We conducted a self-controlled case series study using Japanese health insurance claims data. Exposed cases were identified as those who had experienced both NSAID prescription and acute asthma attack, which was defined as the combination of an inhalation procedure and the prescription of any inhaled β2 -agonist. The incidence rate ratios (IRRs) and 95% confidence intervals (CIs) for NSAID prescription periods compared with baseline periods were calculated using conditional Poisson regression models; COX-2 selective and nonselective NSAIDs were similarly compared. Results: We identified 9769 subjects, more than 95% of whom were younger than 60 years. There was a significantly higher risk of acute asthma attacks during the NSAID prescription period when compared with the baseline period. The quantified IRRs were, in descending order, 93.94 (95% CI, 90.10-97.95) for the prescription start date, 3.96 (95% CI, 3.63-4.33) for 1 to 9 days after the prescription start date, 3.01 (95% CI, 2.78-3.25) for 7 days after the prescription end date, 2.19 (95% CI, 1.82-2.65) for >9 days after the prescription start date, and 1.44 (95% CI, 1.29 -1.61) for 7 days before the prescription start date. There were lower asthmatic risks for COX-2 selective NSAIDs compared with nonselective NSAIDs. Conclusions: The use of NSAIDs in Japan was associated with an increased risk of acute asthma attacks. However, this risk was lower in COX-2 selective NSAIDs.